Common agricultural policy in dissarray: How to get out of the deadlock? - Jörg-Volker Schrader (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
When the CAP was established back in 1958, it was a powerful means for the economic or - even more ambitious - for the political integration of the European Community. In more recent years, however, it has been identified by a growing number of people as both the origin of mismanaged agricultural markets and of political quarrels, both within the Community and with non-member countries. Some of the well-known results of the CAP are the wine lakes and butter mountains, resulting from high guaranteed producer prices. In the summer of 19 87, they surpassed quotations on world markets by the factor of two or three in order of magnitude. Disposing surplusses on either international or national markets through export restitutions or subsidies for an inferior usage (e.g. butter as feed for calves, destination of wine for fuel-alcohol) has proved to be very costly.
Keywords: 330